PHAENOMENA COMO GÉNERO HESIÓDICO - Gallego Real, A. L. (Myrtia, 2004)
In this article we try to emphasize the adaptation made by the Solensian author on the basic rules of the Hesiodic didactic genre, taking Opera et Dies as a reference. Arato masks his work under the pretext of the Hesiodic genre to incorporate a new poetry in the style of Calimachus, full of subtlety and intertextuality. It does not mean that we are going to consider Phaenomena as a mere exercise of imitation; our perspective is to show the peculiar adjustment of the genre guidelines and his Hesiodic background as an act of comprehension and evaluation of Phaenomena’s literary value per se.